2020
DOI: 10.1039/d0ra08153a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen defects on a ferromagnetic CrI3 monolayer

Abstract: This work shows that the natural oxygen defects in the CrI3 monolayer, a first 2D magnet, enrich its structural, electronic, and magnetic properties, offering an effective way of tuning the functionality of CrI3 monolayer and other ultrathin magnets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…22 Note that our calculated J 1 and J 2 values of the CrI 3 monolayer are −1.34 and −0.73 meV as shown in Table 1, where the J 1 value is also in line with the experimental value of −1.42 meV and previous DFT results of −1.33, −1.44, −1.67 and −1.69 meV. 22,30–32 The negative J 1 and J 2 values indicate the long-range FM ordering between the first and second nearest-neighbors at the magnetic ground state.…”
Section: Resultssupporting
confidence: 87%
“…22 Note that our calculated J 1 and J 2 values of the CrI 3 monolayer are −1.34 and −0.73 meV as shown in Table 1, where the J 1 value is also in line with the experimental value of −1.42 meV and previous DFT results of −1.33, −1.44, −1.67 and −1.69 meV. 22,30–32 The negative J 1 and J 2 values indicate the long-range FM ordering between the first and second nearest-neighbors at the magnetic ground state.…”
Section: Resultssupporting
confidence: 87%
“…Recently, Grönke et al 18 found traces of oxygen attributable to surface oxidation of exfoli-ated CrCl 3 flakes during transport in air, but it is not established whether flakes are really prone to oxidation upon air exposure and which are the possible effects of oxygen on the electronic structure. 6,7,19 On the other hand, 2D vdW materials have native structural vacancy-defects 20 that can be exploited by processes such as thermal annealing. 21 Some theoretical studies on Cr-trihalides highlighted the role of defects in determining the electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we considered the FM order and three possible AFM configurations, namely, N éel-AFM, Stripy-AFM, and Zigzag-AFM, which are depicted in Figure 6. After that, by comparing the magnetic energy of these four configurations, J ex could be acquired [5,7], which is listed in Table 3. As shown in Figure 7, our calculated T C of the Cr 2 I 3 F 3 monolayer is about 47 K, which is slightly smaller than that of the CrI 3 monolayer but evidently larger than that of the CrF 3 monolayer.…”
Section: Electronic and Magnetic Propertiesmentioning
confidence: 99%
“…As a good example, the chromium triiodide (CrI 3 ) monolayer is the thinnest intrinsic ferromagnetic material that has been successfully synthesized by the mechanical exfoliation method [4]. Most of the studies about 2D CrI 3 materials have been focused on their ferromagnetic properties, contributing to the opportunity for the development of nano-spintronic devices [5][6][7]. What is even more enticing is that, if a CrI 3 monolayer combines magnetism and piezoelectricity, it will offer considerable potential for integrating microelectronics and spintronics.…”
Section: Introductionmentioning
confidence: 99%